Perbandingan Berbagai Model Peramalan Indeks Harga Saham Gabungan (IHSG) di Masa Pandemi Covid-19 - Bakti Siregar; F. Anthon Pangruruk; Prya Artha Widjaja (Jurnal Multidisiplin Madani, 2022)
The COVID-19 pandemic has a negative impact on various sectors, including the stock market where many people are hesitant to invest in stocks, especially in Indonesia. This condition is due to anxiety and the inability to control random influences in the field of buying and selling shares. However, investors can still get benefits in investing in stocks if every decision is made by using the best model to predict the future trend and determine their optimized portfolio. Therefore, this study aims to compare several models that can forecast the Composite Stock Price Index (IHSG). The results confirmed that the Prophet model is the best. These results are confirmed by observing the MAE, MAPE, MASE, SMAPE, RMSE, and R- squared.